2016
DOI: 10.1007/s00335-016-9671-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genetic basis of primary hypoadrenocorticism in Standard Poodles using SNP array genotyping and whole-genome sequencing

Abstract: Primary hypoadrenocorticism, also known as Addison’s disease, is an autoimmune disorder leading to the destruction of the adrenal cortex and subsequent loss of glucocorticoid and mineralocorticoid hormones. The disease is prevalent in Standard Poodles and is believed to be highly heritable in the breed. Using genotypes derived from the Illumina Canine HD SNP array, we performed a genome-wide association study of 133 carefully phenotyped Standard Poodles (61 affected, 72 unaffected) and found no markers signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
2
9
0
1
Order By: Relevance
“…Genetic predisposition for disease is evident in both dogs and humans [ 1 , 8 , 15 , 16 , 19 , 24 , 25 ], and genes implicated in increased susceptibility to human AD include the major histocompatibility complex ( MHC ) class II genes (haplotypes DR3-DQ2 and DR4-DQ8), cytotoxic T-lymphocyte-associated protein 4 ( CTLA4 ), protein tyrosine-phosphatase non-receptor type 22 ( PTPN22 ), MHC class II transactivator ( CIITA ) [ 19 , 24 , 26 ], and the autoimmune regulator ( AIRE ) gene, which causes an autoimmune polyglandular syndrome that includes AD [ 24 ]. Although canine pedigree studies have indicated a recessive autosomal mode of inheritance for AD in the Standard Poodle and PWD [ 1 , 15 ], a recent genome-wide association study (GWAS) on Standard Poodles failed to demonstrate significant associations with AD, suggesting a more complex mode of inheritance [ 27 ]. Candidate gene approaches have implicated many of the same genes identified in human AD with increased susceptibility to canine AD: CTLA4 in the PWD, Cocker Spaniel and Springer Spaniel [ 10 , 14 , 28 ]; PTPN22 in the Cocker Spaniel [ 10 ]; and the canine MHC (or dog leukocyte antigen, DLA) class II genes in the NSDTR, Bearded Collie and Standard Poodle [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic predisposition for disease is evident in both dogs and humans [ 1 , 8 , 15 , 16 , 19 , 24 , 25 ], and genes implicated in increased susceptibility to human AD include the major histocompatibility complex ( MHC ) class II genes (haplotypes DR3-DQ2 and DR4-DQ8), cytotoxic T-lymphocyte-associated protein 4 ( CTLA4 ), protein tyrosine-phosphatase non-receptor type 22 ( PTPN22 ), MHC class II transactivator ( CIITA ) [ 19 , 24 , 26 ], and the autoimmune regulator ( AIRE ) gene, which causes an autoimmune polyglandular syndrome that includes AD [ 24 ]. Although canine pedigree studies have indicated a recessive autosomal mode of inheritance for AD in the Standard Poodle and PWD [ 1 , 15 ], a recent genome-wide association study (GWAS) on Standard Poodles failed to demonstrate significant associations with AD, suggesting a more complex mode of inheritance [ 27 ]. Candidate gene approaches have implicated many of the same genes identified in human AD with increased susceptibility to canine AD: CTLA4 in the PWD, Cocker Spaniel and Springer Spaniel [ 10 , 14 , 28 ]; PTPN22 in the Cocker Spaniel [ 10 ]; and the canine MHC (or dog leukocyte antigen, DLA) class II genes in the NSDTR, Bearded Collie and Standard Poodle [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, imputation is the most cost-effective option and has been used successfully in human and cattle GWAS, especially with the recent WGS efforts in these species [11,12]. Imputation has also been used in a canine within-breed GWAS of primary hypoadrenocorticism in the Standard poodle, resulting in an approximately 20-fold increase in SNP number, although this did not lead to the identification of a significant association [13].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome-wide gene expression studies have been performed for many diseases in both human and veterinary medicine [ 29 32 ]. These studies have proven powerful in informing disease pathophysiology, identifying causative genes, and discovering novel therapeutic targets [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gaining a better understanding of the pathophysiology of IMHA may lead to new treatment options and better clinical outcomes for canine patients, and improve the usefulness of the dog as a model for the analogous human disease. Transcriptome-wide gene expression studies have been performed for many diseases in both human and veterinary medicine [29][30][31][32]. These studies have proven powerful in informing disease pathophysiology, identifying causative genes, and discovering novel therapeutic targets [33][34][35].…”
Section: Introductionmentioning
confidence: 99%